Methylation status of CDH1 gene in samples of gastric mucous from brazilian patients with chronic gastritis infected by Helicobacter pylori - Kague, Erika [UNESP]; Thomazini, Cristiane Melissa [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; Carvalho, Fabrício de; Leite, Celso Vieira de Souza [UNESP]; Pinheiro, Nídia Alice [UNESP] (Instituto Brasileiro de Estudos e Pesquisas de Gastroenterologia (IBEPEGE), 2010)
CONTEXTO:O câncer gástrico é uma das principais neoplasias que causam o óbito no Brasil e no mundo. Helicobacter pylori é um carcinógeno do tipo I relacionado à gastrite crônica. Diferenças no grau de virulência de suas cepas levam a maior risco de desenvolvimento de doenças gástricas. A metilação de ilhas CpGs está envolvida com o processo de tumorigênese em diferentes tipos de câncer. CDH1 é um gene supressor tumoral que, quando inativado, pode aumentar as chances de metástase. A metilação deste gene em estágios precoces da carcinogênese gástrica ainda não é totalmente compreendida. OBJETIVO: Investigar o padrão de metilação do gene CDH1 em amostras de gastrites crônicas e correlacionar com a presença do H. pylori. MÉTODOS: Foram usadas 60 biopsias de mucosas gástricas. A detecção de H. pylori foi realizada por PCR para o gene da urease C e a genotipagem com PCR para os genes cagA e vacA (região s e m). O padrão de metilação do gene CDH1 foi analisado usando a técnica de PCR e específica para a metilação e sequenciamento direto dos produtos de PCR. RESULTADOS: A bactéria H. pylori foi detectada em 90% das amostras de gastrites crônicas; destas, 33% portavam o gene cagA e 100% vacA s1. O genótipo vacA s2/m1 não foi detectado nas amostras analisadas. Metilação de CDH1 foi detectada em 63,3% das amostras de gastrites e 95% delas eram portadoras de H. pylori. CONCLUSÃO: Os resultados deste estudo sugerem que a metilação em CDH1 e a infecção pelo H. pylori são eventos frequentes em amostras de pacientes brasileiros com gastrite crônica e reforça a correlação entre infecção por H. pylori e inativação do gene CDH1 em estágios precoces da tumorigênese gástrica.

CONTEXT: Gastric cancer is one of the top list of cancer types that most leads to death in Brazil and worldwide. Helicobacter pylori(H. pylori) is a class I carcinogen and infect almost 90% of chronic gastritis patients. Some genotypes confer different virulent potential to H. pylori and can increase the risk of gastritis development. Methylation of CpG islands can inactivate tumor suppressor genes and therefore, it can be involved in the tumorigenic process. CDH1 is a tumor suppressor gene that encodes the E-cadherin protein, which is important in maintaining cell-cell contacts. The inactivation of this gene can increase the chance of metastasis. Promoter methylation of CDH1 at early steps of gastric carcinogenesis is not yet completely understood. OBJECTIVE: In this study, we investigated the methylation status of CDH1 in chronic gastritis samples and correlated it with the presence of H. pylori. METHODS: Sixty gastric mucosal biopsies were used in this study. The detection of H. pylori was performed with the PCR primers specific to urease C gene. H. pylori genotyping was performed by PCR to cagA and vacA (s and m region). The methylation status of these gene CDH1 was analyzed using methylation-specific polymerase chain reaction and direct sequencing of the PCR products was performed using primers methylated and unmethylated in both forward and reverse directions. RESULTS: H. pylori was detected in 90% of chronic gastritis samples; among these 33% were cagA positive and 100% vacA s1. The genotype vacA s2/m1 was not detected in any sample analyzed. Methylation of CDH1 was detected in 63.3% of chronic gastritis samples and 95% of them were also H. pylori-positive. CONCLUSION: This work suggests that CDH1 gene methylation and H. pylori infection are frequent events in samples from Brazilian patients with chronic gastritis and reinforces the correlation between H. pylori infection and CDH1 inactivation in early steps of gastric tumorigenesis.
Keywords: Infecções por helicobacter; Gastrite; Caderinas; Metilação; Helicobacter infections; Gastritis; Cadherins; Methylation